ANALISIS SERVQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS PADA JALAN TOL RUAS CENGKARENG-BATUCEPER-KUNCIRAN - Pratala, Esaka; Supriyadi, Yudi Nur; Saragih, Guntur Syahputra (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The Cengkareng-Batuceper-Kunciran toll road is one of the National Strategic Projects managed by Jasamarga Kunciran Cengkareng Limited Liability Company, this study aims to analyze the quality of service on the Cengkareng-Batuceper-Kunciran toll road using the service quality method. The toll road service attributes used are the dimensions of reliability, responsiveness, assurance, empathy, and tangible. Meanwhile, Importance Performance Analysis is used to identify service quality attributes that are a priority for improving toll road services. The results of the analysis of the dimensions of reliability and responsiveness have not met the expectations of toll road users. The results of the Importance Performance Analysis, the attributes that are priority services are the attributes in Quadrant I consisting of Safety, Information Accuracy and Accident Handling. Meanwhile, what needs to be maintained are the attributes in Quadrant II consisting of Smoothness, Smoothness of the toll road, Quality of Service of Substations Without People, and Road Damage Repair. Attributes with low priority in Quadrant III consist of the speed of emergency services, the shape and appearance of information boards, traffic signs and markings and street lighting. Excessive services in Quadrant IV consist of Security from crime on the toll road, Ease of getting emergency services, and Call Center